2022
DOI: 10.1039/d2ta03099c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Fe2P/Co embedded trifunctional electrocatalyst for high-performance anion exchange membrane fuel cells, rechargeable Zn–air batteries, and overall water splitting

Abstract: Designing highly active multifunctional catalysts to meet the demands for fuel cells, metal-air batteries and water-splitting devices is a top priority. Here, an efficient and novel trifunctional electrocatalyst (Fe2P/Co@NPC) with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The presence of Ni 2 P, NiS 2 , and Fe 2 P metal nanoparticles is attributed to the introduction of P and S elements during the synthesis of the NiFePS/CNT@NF catalyst, leading to complex high-temperature reactions. From the reported literature, transition metal phosphides (TMPs) (TM = Fe, Co, Cu, Ni, W, and Mn) exhibit relatively excellent electrocatalytic activity for HER and OER. According to research by Kong et al, the coordination structure of transition metal disulfides is similar to the active center of hydrogenase, facilitating the HER process. Previous studies have confirmed the excellent catalytic activity of NiS 2 in the HER.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Ni 2 P, NiS 2 , and Fe 2 P metal nanoparticles is attributed to the introduction of P and S elements during the synthesis of the NiFePS/CNT@NF catalyst, leading to complex high-temperature reactions. From the reported literature, transition metal phosphides (TMPs) (TM = Fe, Co, Cu, Ni, W, and Mn) exhibit relatively excellent electrocatalytic activity for HER and OER. According to research by Kong et al, the coordination structure of transition metal disulfides is similar to the active center of hydrogenase, facilitating the HER process. Previous studies have confirmed the excellent catalytic activity of NiS 2 in the HER.…”
Section: Resultsmentioning
confidence: 99%
“…2 b , d ,5 To alleviate the gas mixing issues (H 2 and O 2 ), proton exchange membrane (PEM) water electrolysis and anion exchange membrane (AEM) water electrolysis are considered as promising water electrolyzers for industrial level application, where the AEM water electrolyzer can operate in an alkaline environment but the PEM water electrolyzer may require acid-stable OER electrocatalysts to operate in an acid environment, which can elevate the cost. 6 Therefore, various promising strategies such as improving the gas-evolution behavior, enhancing the conductivity, tuning the electronic structure, increasing the electrochemical surface area, surface reconstruction during the HER/OER, preparing core–shell/hetero/hollow structured materials, preparing amorphous materials, fabricating bimetallic/multi-metallic materials, doping metals/heteroatoms, preparing porous/nanostructured/quantum sized materials, and creating oxygen vacancies/defects are used to achieve high-performance noble metal-free electrocatalysts for the HER and/or OER in an alkaline environment. 5,7…”
Section: Introductionmentioning
confidence: 99%
“…Among transition-metal-based electrocatalysts, Ni-based and Fe-based electrocatalysts have attracted much attention because of their general availability, and the Co element tends to play a role in bimetallic-based electrocatalysts, forming a synergistic effect with other transition metals and bringing about the improvement of catalytic activity for the oxygen evolution reaction [ 30 , 31 , 32 ]. By introducing other transition metal compounds to form multi-metal-based electrocatalysts, the catalytic activity of the oxygen evolution reaction can be effectively improved.…”
Section: Introductionmentioning
confidence: 99%